History, Context, and Multidisciplinarity - POLAT, MUHAMMED SAİD (My University, 2022)
History is a discipline that studies the past. Everything that belongs to the past is the subject of history. Everything from an object to a symbol, events and persons are included in the subject of history. The discipline of history studies these things mostly from texts. It tries to reveal whatever information there is about the things researched in the texts. But everything in the past has a broad context, and these things make sense with context. As a matter of fact, in order for any war to be understood and explained well, the context of that war must be well known. Without studying its context, the historian can extract information about a war from texts in languages he knows. But when the context is well known, information and knowledge about war expands considerably. How that war happened in history, it becomes possible to determine and evaluate it more closely.. Here, the historical context of anything can be best understood and explained when studies are carried out with more than one discipline. One of these ways of studying is multidisciplinary study. Multidisciplinary study has advantages as well as disadvantages compared to other multi disciplinary studies. Especially in countries like Turkey where disciplinary studies are still common, multidisciplinary studies can be done more easily. Because researchers who are accustomed to studying in a discipline and who care about it can participate in stduy on a common subject by preserving these features in multidisciplinary studies. From this point of view, multidisciplinary studies seem to be the most appropriate type of study for researchers and historical studies in Turkey for now, when the issue is approached specifically for the discipline of history. In this paper, the relationship between history, context and multidisciplinary will be revealed. Keywords: History, Multidisciplinarity, Context, Historiography
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); History; Multidisciplinarity; Context; Historiography